New species and new behavioral data of Phlugiola Karny, 1907 (Orthoptera: Tettigoniidae: Meconematinae) from the Brazilian Amazonian Rainforest - Mendes, Diego Matheus De Mello; Oliveira, Jomara Cavalcante De; Alves-Oliveira, João Rafael; Rafael, José Albertino (Zootaxa, 2017)
Phlugiola Karny, 1907 is a genus of small predatory katydids with six included species distributed in Brazil, Bolivia, Colombia, Peru and Suriname. In this paper two new Brazilian species are described, Phlugiola longipedes sp. nov. (type locality: Amazonas, Tefé) and Phlugiola igarape sp. nov., (type locality: Acre, Bujari) both from tropical rainforests. Behavioral data and natural history notes are provided.